Migrants and refugees between sociology and law: Mental health and integration strategies for the most fragile individuals - Salvatore Piliu (Journal of Modern Science)
Objectives The contribution aims to carry out a socio-anthropological and juridical analysis of the issues concerning the status of migrants and refugees, in order to identify the strategies prepared by the Italian State regarding the protection of the mental health of migrants and refugees and the prospects for integration and legal protection of the most fragile subjects.